2015
DOI: 10.1002/hbm.22880
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of age with volume and microstructure of hippocampal subfields in healthy older adults

Abstract: Hippocampal atrophy in advanced healthy aging has frequently been reported. However, the vulnerability of different hippocampal subfields to age-related atrophy is still a source of debate. Moreover, the association of age with the microstructural integrity of subfields is largely unknown. In this study, we investigated the associations between age and volume as well as microstructural integrity of hippocampal subfields using a three-dimensional (3D) surface mapping approach. Forty-three healthy older adults s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 76 publications
6
28
0
3
Order By: Relevance
“…The age-relationships of volume and MD were not weakened the least by including both in the same model. Even though not previously addressed in a lifespan sample, this finding is in line with previous studies showing that micro- and macrostructural measures of hippocampal subfields are complementary in their aging-relationships (Pereira et al, 2014; Wolf et al, 2015). Thus, the cellular processes responsible for the micro-and macro-structural changes in hippocampal sub-regions across life appear to be completely unrelated.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The age-relationships of volume and MD were not weakened the least by including both in the same model. Even though not previously addressed in a lifespan sample, this finding is in line with previous studies showing that micro- and macrostructural measures of hippocampal subfields are complementary in their aging-relationships (Pereira et al, 2014; Wolf et al, 2015). Thus, the cellular processes responsible for the micro-and macro-structural changes in hippocampal sub-regions across life appear to be completely unrelated.…”
Section: Discussionsupporting
confidence: 89%
“…Both aHC and pHC volume and MD were strongly and independently related to age through the lifespan, with better model fits for aHC suggesting a somewhat tighter relationship with age. While studies of adults have shown increases in hippocampal MD with age (Anblagan et al, 2018); den Heijer et al (2012); (Pereira et al, 2014; Wolf et al, 2015), we are not aware of any lifespan studies of hippocampal microstructure. The volumetric findings are in line with previous developmental studies showing differential (DeMaster et al, 2014; Lin et al, 2013; Riggins et al, 2018; Wang et al, 2003; Yang et al, 2013) and non-linear (Daugherty et al, 2017; Gogtay et al, 2006) age-relationships for sub-regions along the AP axis.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The Bayesian inferential method deployed on FreeSurfer 6.0 has not been robustly validated against a gold standard method, such as manual segmentation (Wolf et al, 2015). Furthermore, even with ultra-high resolution MRI, there are boundaries such as the interfaces between the CA fields along the pyramidal layer of the hippocampus or the CA4/GC-DG interface that cannot be seen.…”
Section: Discussionmentioning
confidence: 99%